Studio Notes - Jantjes, Ulriche (Michaelis School of Fine Art, 2024)
My current research project is concerned with the Moravian mission settlement of Elim, as established by German missionaries in 1824, and situated in close proximity to Bredasdorp in the Overberg region of the Western Cape. I identify with this specific mission settlement as a descendant who acknowledges their ancestral lineage rooted in the history of the community. For this reason, I utilise my artwork to reflect on the specificity of my cultural heritage which stems from the German mission settlement in South Africa. In practice, I contemplate my dual heritage by acknowledging a mission heritage, and an indigenous heritage which predates missionary work in the region. By means of drawing, painting, sculpture, and printmaking, I consider my heritage with reference to scholarship related to Homi K. Bhabha, and his writing on culture in the post colony. Here, I employ Bhabha's deliberation on ‘the beyond' to contextualise my creative praxis as a point of contemplating alternative perspectives on a heritage entwined with cultural erasure. For this body of work, I situate the distinct features of Elim, such as the historic buildings, old watermill, and visual traditions (such as whitewashing), as a crucial part of my visual language. I utilise the cultural and aesthetic traditions as visual and material metaphors in my creative praxis. By examining Homi K. Bhabha's theoretical concepts, in relation to my creative praxis, I have intermingled ideas to create the framework from which I developed this body of work.